Problems of Tapping the International Experience of Social Services in Present-Day Russia - BUYANOVA, Marina O. (Journal of Advanced Research in Law and Economics, 2017)
The article discusses problems of reforming the social security system in modern-day Russia, taking into consideration international experience. It is argued that tapping the international experience of social work must not be direct imitation of forms and methods of work but through careful analysis and both long-term and short-term planning as well as identifying specific elements in the international experience that can be applied in Russia at present. The article provides evidence in support of forming a system of social services in Russia using the experience of social services in Western European countries using the theory of convergence. Based on the experience of social services in the USA, Germany, Great Britain, the countries of Scandinavia, Italy, France, Portugal, Luxembourg and other countries, the article presents the most suitable ways of organizing social services, identifying the strata of population eligible for social services as well as the amount and the forms of social services provided. The article explores the possibility of changing the system of funding of social services. It is concluded that due to the present economic situation in Russia, drawing on the experience of social services of leading industrialized countries in this country is but a distant prospect.